Basic and clinical science course 1998-1999. Section 2, Fundamentals and principles of ophthalmology (American Academy of Ophthalmology, 1998)
The textbook focuses on basic and clinical science, and ophthalmology. Intended for professional public and for university students.
Keywords: věda a výzkum; klinické lékařství; Clinical Medicine; věda; Science; Ophthalmology; oftalmologie